PENGEMBANGAN KOMPETENSI SUMBER DAYA MANUSIA DALAM MENDUKUNG TATA KELOLA ORGANISASI OLAHRAGA KEBUGARAN PADA PENGURUS ORKI KOTA TANGERANG SELATAN - Aprilia Astuti; Yeni Liana Sari; Denies Susanto (Abdi Jurnal Publikasi, 2026)
This Community Service Program (PKM) was carried out with the aim of enhancing the competence of human resources (HR) among the board members of Olahraga Kebugaran Indonesia (ORKI) in South Tangerang City to support the governance of fitness organizations. The main problems faced by ORKI included limited managerial knowledge, insufficient modern administrative skills, and weak coordination among board members. The implementation method involved training through workshops, case simulations, role plays, and group discussions. The training materials covered organizational strategic planning, digital-based administration management, participative leadership, and transparent and accountable organizational governance. Evaluation was conducted through pre-tests, post-tests, observations, and participant feedback.The results of the program indicated a significant improvement in the ability of ORKI board members to manage the organization professionally, transparently, and competitively. The program also fostered the development of a collaborative work culture, discipline, and stronger accountability. Therefore, this PKM made a tangible contribution to strengthening the governance of fitness organizations in South Tangerang.